Views on Amyloid Hypothesis and Secretase Inhibitors for Treating Alzheimer's Disease: Progress and Problems - Nguyen, Jeffrey-Tri; Yamani, Abdellah; Kiso, Yoshiaki (Current Pharmaceutical Design, 2006)
Alzheimer's disease is a form of sporadic, age-related dementia. According to the “amyloid hypothesis”, the processing of β-amyloid precursor protein (APP) leads to the formation of senile plaque aggregates which subsequently congest normal neurological functions. Currently, prophylaxis is testimonial, while treatment relies mainly on symptomatic relief. This review emphasizes the importance of disrupting the pathological processing of APP via α-secretase activators, β- and γ-secretase inhibitors, and compounds that bind APP. The style of writing should appeal to those with strong interests in medicinal chemistry with an equal balance of medicine and chemistry.
Keywords: Alzheimer' s disease